(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The system mainly contains two modules one is Information System and the other is Expert Advisory system. The Information System contains the static information about different diseases in the field of Nephrology. This information system helps the patients /users to know about the problems related to kidneys. The Nephrology Advisory system helps the Patients /users to get the required and suitable advice depending on their queries.This research describes how the neural computing system designed to support the medical decision process using medical imaging databases and creating the optimal systems for ministry of the health to help the physician to making the correct decision with high certainty also give suitable medical device and can use for training the medical stuff easily either in hospital or in the clinical center. the main aim of the proposed system is the ability to diagnose of the kidney disease by questionnaire and clinical data of the patient. The proposed system makes a differential diagnosis among the main kidney diseases. The diagnosis is made taking into account the clinical exam (the symptoms that can be seen of felt) and the preclinical exam (the results of laboratory tests). This system is designed to give help to a medical expert (doctor) in making the appropriate diagnosis of a patient. The kidney diseases have a lot of common symptoms and many of them are very much alike, and that makes it very difficult even for a kidney doctor (specialist) to put a right diagnosis. The main operation of the proposed system is ability to diagnosis kidney disease by using symbol and friendly user interface and also has ability to explain the result and the answer of most two questions how the proposed system reaches to the results and why the proposed system to reaches to this results.